Culture and the Independent Self: Obstacles to environmental sustainability?. (June 2019) - Komatsu, Hikaru; Rappleye, Jeremy; Silova, Iveta
Highlights: This paper reports an empirical link between culture and human impacts on Earth. Countries where individualism is dominant tend to deny anthropogenic climate change. The same countries have a relatively high Ecological Footprint. Shifting cultures away from individualism might be necessary for sustainability. Abstract: The centrality of culture for achieving environmental sustainability has long been underscored by philosophers, psychologists, and social scientists concerned about the environment. However, to date few studies have detected an empirical relationship between cultural dimensions and actual environmental impacts on Earth (e.g., the Ecological Footprint, EF). This study examined the hypothesis that an individualistic society, herein defined as one whose members predominantly believe in forms of independent self-construal, would exhibit a higher environmental impact compared to a less individualistic society, herein defined as one where the prevailing belief is in interdependent selfhood. This study tested three sub-hypotheses. First, due to the dominance of the independent self, people in an individualistic society tend to be less inclined to believe that human activities cause environmental problems (i.e., lower levels of anthropogenic perception). Second, these low levels of anthropogenic perception prevent members of individualistic societies from consciously organizing pro-environmental behavior, resulting in a higher environmental impact. Third, even among countries with similar levels of anthropogenic perception, those in individualistic societies would exhibit higher environmental impacts due to less self-control when facing trade-offs between individual and social benefits. To examine these hypotheses, the study used three indices comprising country-level data including Hofstede's 'individualism-collectivism' scale, EF, and anthropogenic perception of climate change. Results confirm higher EF for more individualistic countries, supporting the main hypothesis and confirming positive results for all subhypotheses. The findings suggest that although the independent self has traditionally been a major cornerstone of western civilization and been valorized in other places worldwide during the modern era, rewriting this culturally-derived concept of self might now be necessary to move towards greater environmental sustainability